Inclusive Education for Exceptional Children in Egypt and the US: Reforming Egyptian Inclusive Education System in Post-pandemic World - Noha Abbas (Gulf Education and Social Policy Review)
Inclusive education means that exceptional children (EC) can fully participate in the learning process alongside their typically developing peers, supported by reasonable accommodations and teaching strategies that are tailored to meet their individual needs. The main goal of inclusion policies for EC is to provide high-quality education for all without discrimination and to ensure the implementation of equal opportunity principles. The primary purpose of this study is to explore the reality of inclusive education systems in Egypt and the United States (US) and to develop a better understanding of similarities and differences and thus identify the lessons learned. The study applied a comparative analysis method. Research findings revealed that the progress towards inclusion practices in Egyptian inclusive public schools is minimal and hindered by many challenges. Among them are lacking financial resources and a shortage of qualified teachers trained to differentiate curricula for EC. Based on the research findings, the study concludes with recommendations to improve the Egyptian inclusive education for EC.